Monocyte subpopulations display disease-specific miRNA signatures depending on the subform of Spondyloarthropathy - Stec, Małgorzata; Czepiel, Marcin; Lenart, Marzena; Piestrzyńska-Kajtoch, Agata; Plewka, Jacek; Bieniek, Agnieszka; Węglarczyk, Kazimierz; Szatanek, Rafał; Rutkowska-Zapała, Magdalena; Guła, Zofia; Kluczewska, Anna; Baran, Jarosław; et al. (Frontiers in Immunology, 2023)
Spondyloarthropathies (SpA) are a family of rheumatic disorders that could be divided into axial (axSpA) and peripheral (perSpA) sub-forms depending on the disease clinical presentation. The chronic inflammation is believed to be driven by innate immune cells such as monocytes, rather than self-reactive cells of adaptive immune system. The aim of the study was to investigate the micro-RNA (miRNA) profiles in monocyte subpopulations (classical, intermediate and non-classical subpopulations) acquired from SpA patients or healthy individuals in search for prospective disease specific and/or disease subtype differentiating miRNA markers. Several SpA-specific and axSpA/perSpA differentiating miRNAs have been identified that appear to be characteristic for specific monocyte subpopulation. For classical monocytes, upregulation of miR-567 and miR-943 was found to be SpA-specific, whereas downregulation of miR-1262 could serve as axSpA-differentiating, and the expression pattern of miR-23a#, miR-34c, mi-591 and miR-630 as perSpA-differentiating markers. For intermediate monocytes, expression levels of miR-103, miR-125b, miR-140, miR-374, miR-376c and miR-1249 could be used to distinguish SpA patients from healthy donors, whereas the expression pattern of miR-155 was identified as characteristic for perSpA. For non-classical monocytes, differential expression of miR-195 was recognized as general SpA indicator, while upregulation of miR-454 and miR-487b could serve as axSpA-differentiating, and miR-1291 as perSpA-differentiating markers. Our data indicate for the first time that in different SpA subtypes, monocyte subpopulations bear disease-specific miRNA signatures that could be relevant for SpA diagnosis/differentiation process and may help to understand SpA etiopathology in the context of already known functions of monocyte subpopulations.